TEORI AGENSI DAN TEORI STEWARSHIP DALAM PERSPEKTIF AKUNTANSI - Eko Raharjo (STIE Pelita Nusantara Semarang, 2007)
The agency theory tries to compose formal link between principal and agent or any intended parties within budget composition process. This theory imposes on achievement measurement design and reward provided for manager to act positively and or profitable for company in a whole.The theorem of agency theory never implements all situations. Such alternative models of behaviour and managerial motivation is stewardship theory, which gained from psychologically and sociologically traditions. This research increased the meaning of stewardship theory through description of terminology and theoretically contribution.Also adding within the previous stewardship theory through tested such model that relies on manager chosen – the better principal than such determination view. Based on the existed model, manager chose to act as steward or agent. Their choosing was various in line with their psychology motivation and perception about existed situation. Principal also chose to create some agency orstewardship linkage, depend on the perception about its situation and manager. If whether manager or principal feels that the other parties will act in defend position, then the best benefit will be act as agency, and organization will receive optimally return upon its investment. But if both parties chose to develop stewardship linkage, then the organization will realize maximum rewards.